Integrating climate change in infrastructure project appraisal A proposed methodology for Ireland - Percoco, Marco (OECD Working Papers on Public Governance, 2023)
Infrastructure plays a pivotal role in achieving climate neutrality and resilience. However, infrastructure is also vulnerable to certain risks, and poor management of infrastructure assets can lead to increased dependency on fossil fuels and lock in climate-related risks. For this reason, an infrastructure governance framework is needed that can direct public investments towards sustainability objectives. To this end, the OECD has provided technical support to the Government of Ireland to strengthen climate-related and environmental considerations in public infrastructure decision making (i.e. strategic planning, project appraisal, budgeting). Building on Irish Public Spending Code and on standardised criteria based on international good practices, this working paper develops a new methodological approach to assessing the climate-related impacts of infrastructure and integrate climate-related risk and uncertainty in the appraisal of infrastructure projects